Проблемы выбора комплексной системы класса CAD/CAM/CAE/CAPP/PDM/PLM на машиностроительном предприятии - Кохановский, В. И.; Кохановская, Ольга Владиславовна (НТУ "ХПИ", 2009)
Мета статті полягає у розробці рекомендацій для вибору концепції комплексної системи автоматизації машинобудівного підприємства на основі аналізу існуючого програмного забезпечення інтегрованих систем класу CAD/CAM/CAE/CAPP/PDM/PLM.

The purpose of this paper consists in development of recommendations for the choice of conception of the comprehensive system of machine-building enterprise automation on the basis of analysis of existent software of the integrated systems of CAD/CAM/CAE/CAPP/PDM/PLM - class.
Keywords: CAD-система; программное обеспечение; комплексная система автоматизации; числовое программное управление; ЧПУ; КСА; технологическая подготовка производства